On the “-Core” Mechanisms of Street Fashion - Anna Kamneva (ZoneModa Journal, 2020)
This paper introduces a model of vestimentary coordination and synchronization, derived from interdisciplinary research within the tension field of fashion and media studies, dealing with the phenomenon of self-organization in social and cultural systems and exploring the spatiotemporal dynamics of persistence and innovation in the field of democratized postmodern vestimentary fashions. Using the example of the ‘-core’ hype cycle (2000’s hipster, turned normcore, turned glamcore, turned GORPcore), I will outline its two complementary mechanisms providing structural patterns for vestimentary coordination, based on space-biased vestimentary interactions, and synchronization, based on time-biased vestimentary practices: spatialization with a tendency to uniformity-oriented network building and temporalization with a tendency to singularity-oriented swarming. I will argue that the model can serve as analytical tool for describing trend development in a digital culture, characterized by pluralization, differentiation, acceleration and algorithmicity.